Fingerprint of the first stars: multi-enriched extremely metal-poor stars in the TOPoS survey. Issue 1 (15th October 2018) - Hartwig, Tilman; Ishigaki, Miho N; Klessen, Ralf S; Yoshida, Naoki
ABSTRACT: Extremely metal-poor (EMP) stars in the Milky Way inherited the chemical composition of the gas out of which they formed. They therefore carry the chemical fingerprint of the first stars in their spectral lines. It is commonly assumed that EMP stars form from gas that was enriched by only one progenitor supernova ('mono-enriched'). However, recent numerical simulations show that the first stars form in small clusters. Consequently, we expect several supernovae to contribute to the abundances of an EMP star ('multi-enriched'). We analyse seven recently observed EMP stars from the TOPoS survey by applying the divergence of the chemical displacement and find that J1035+0641 is mono-enriched ($p_mono=53{{\ \rm per\ cent}}$ ) and J1507+0051 is multi-enriched ($p_mono=4{{\ \rm per\ cent}}$ ). For the remaining five stars, we cannot make a distinct prediction ($p_mono \lesssim 50{{\ \rm per\ cent}}$ ) due to theoretical and observational uncertainties. Further observations in the near-UV will help to improve our diagnostic and therefore contribute to constrain the nature of the first stars.